Amygdaloidal and other Cavity Filling Zeolites of Kuh-e-Aradeh, Central Iran (Journal of Sciences, Islamic Republic of Iran)
Amygdaloidal, cavity- and fracture-filling zeolites in Eocene volcanic rocks from the Kuh-e-Aradeh of southern Kahrizak, in the northernmost part of Central Iran have been studied in some detail by optical, chemical analysis, SEM, and XRD techniques. The zeolites identified, in order of their relative time of formation from early to late, are tetranatrolite, analcime, natrolite, mesolite, stilbite-Ca, scolecite and heulandite-Ca. Formation of zeolites in the studied region began with a sodium zeolite of low Si/Al ratio and, with the gradual increase in calcium content and Si/Al ratio, ended with calcium zeolites. The zeolites were probably formed as a result of the late-stage hydrothermal activity in 60-150°C spans. Other associated secondary minerals in the region are calcite, opal, quartz, and pyrolusite. Chemical analysis of the host rocks showed that they are mostly andesitic, or, to a lesser extent basaltic, and the composition of one zeolite-bearing dyke is potassic trachybasalt.